2022
DOI: 10.1007/s00339-022-06015-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multi-wavelength ultrafast laser texturing and autoclave sterilization on titanium alloy-based surface wettability

Abstract: Titanium alloys are widely used in bio-medical applications for their excellent bio-compatibility and superior mechanical strength. On the other hand, femtosecond laser processing is a robust versatile and industrial method widely used for surface functionalization. In this work, laser-induced periodic surface structures (LIPSS) on titanium alloy (Ti6Al4V) using different laser wavelengths of 1030 nm (IR), 515 nm (Green) and 257 nm (UV) were created and their surface wettability (physical parameter correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that a decrease in laser wavelength is linked to the generation of smaller structures in the context of LIPSS. [ 114,115 ] In the domain of 2D‐LIPSS, encompassing both types I and II, these questions remain intriguing and merit thorough investigation. Particularly, it is yet to be determined whether 2D‐LIPSS‐I could achieve a scale similar to that of 2D‐LIPSS‐II through laser wavelength reduction.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…Previous studies have shown that a decrease in laser wavelength is linked to the generation of smaller structures in the context of LIPSS. [ 114,115 ] In the domain of 2D‐LIPSS, encompassing both types I and II, these questions remain intriguing and merit thorough investigation. Particularly, it is yet to be determined whether 2D‐LIPSS‐I could achieve a scale similar to that of 2D‐LIPSS‐II through laser wavelength reduction.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…Laser ultra-high precision processing of materials has been widely known for more than five decades. More specifically, the generation of Laser-Induced Periodic Structures (LIPSS or ripples) is a universal phenomenon paving the way for numerous applications 1 , such as tuning the wettability of surfaces 2,3 , adding anti-bacterial functionalities 2,4 , or controlling cell adhesion [5][6][7][8] . Femtosecond lasers can generate LIPSS on surfaces with a periodicity that depends on the irradiation wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…When the LSFL exhibit a period Λ L larger than half of the laser irradiation wavelength λ i /2, generally oriented perpendicular to the laser polarization, the HSFL show a periodicity Λ H lower than half of the laser irradiation wavelength. Using shorter irradiation wavelength results in lower ripple periodicity, for both LSFL and HSFL, and recent cutting-edge developments in ultraviolet (UV) fs lasers unlock sharper surface structuring with enhanced optical, chemical or mechanical effects 3,[10][11][12] . To characterized these nanostructures Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) are the gold standard tools but are challenging on dielectric or fragile samples that cannot be metalized or when LIPSS amplitude is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Laser ultra-high precision processing of materials has been widely known for more than five decades. More specifically, the generation of Laser-Induced Periodic Structures (LIPSS or ripples) is a universal phenomenon paving the way for numerous applications 1 , such as tuning the wettability of surfaces 2 , 3 , adding anti-bacterial functionalities 2 , 4 , or controlling cell adhesion 5 8 . Femtosecond lasers can generate LIPSS on surfaces with a periodicity that depends on the irradiation wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…When the LSFL exhibit a period larger than half of the laser irradiation wavelength , generally oriented perpendicular to the laser polarization, the HSFL show a periodicity lower than half of the laser irradiation wavelength. Using shorter irradiation wavelength results in lower ripple periodicity, for both LSFL and HSFL, and recent cutting-edge developments in ultraviolet (UV) fs lasers unlock sharper surface structuring with enhanced optical, chemical or mechanical effects 3 , 10 – 12 . To characterize these nanostructures Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) are the gold standard tools but are challenging on dielectric or fragile samples that cannot be metalized or when LIPSS amplitude is of interest.…”
Section: Introductionmentioning
confidence: 99%